Modification of Organic Dyes Cnidoscolus Aconitifolius Chlorophyll Hybrid with Dye Synthetic N719 with TiO2 Semiconductor Combination to Improve DSSC-Solar Cell Performance - Pote, Fernince Ina; Dilak, Hory Iramaya (Fakultas Matematika dan Ilmu Pengetahuan Alam, Univetsitas Tanjungpura, 2026)
This research Solar energy is a renewable and environmentally friendly alternative energy source with enormous potential to be converted into electricity through Dye Sensitized Solar Cell (DSSC) technology. The efficiency of DSSC depends strongly on the sensitizer, semiconductor layer, and counter electrode. In this study, the effect of modifying organic chlorophyll dye extracted from Cnidoscolus aconitifolius, hybridized with synthetic dye N719, and combined with the semiconductor TiO₂ was investigated to enhance DSSC performance. The fabrication process employed low-cost methods, including spin coating, slip casting, drop casting, and soaking techniques, to obtain homogeneous TiO₂ thin films and maximize dye adsorption. Optimization of temperature and soaking duration was carried out to support the formation of crystal size, morphology, and anatase phase of TiO₂, which are crucial for electron transport. The counter electrode was prepared with Pt (Hexachloroplatinic (IV) acid 10%), functioning as an effective catalyst to accelerate redox reactions with the electrolyte. Performance testing using a Keithley instrument revealed that the hybrid dye N719: Cnidoscolus aconitifolius with a concentration of 0.1% wt achieved the highest conversion efficiency of 0.82%. The absorption spectrum confirmed that the hybrid dye effectively absorbed light in the range of 400–800 nm, demonstrating the synergistic role of natural and synthetic dyes in improving photocurrent generation. This research provides insights into the utilization of chlorophyll-based natural dyes from Cnidoscolus aconitifolius combined with synthetic dyes to produce eco-friendly DSSCs and highlights the potential of fabrication techniques to reduce production costs and supports the development of sustainable solar cell technologies.